2021
DOI: 10.3390/nu13114106
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Breast Cancer Risk in Black Urban South African Women: The SABC Study

Abstract: A total of 396 breast cancer cases and 396 population-based controls from the South African Breast Cancer study (SABC) matched on age and demographic settings was included. Validated questionnaires were used to collect dietary and epidemiological data. Dietary patterns were derived using principal component analysis with a covariance matrix from 33 food groups. Odds ratios and 95% confidence intervals were estimated using conditional logistic regression. A traditional, a cereal-dairy breakfast and a processed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…In this study, several patterns have been identified: a traditional pattern (composed of poultry, organ and offal meat, mono-and polyunsaturated fats, soup powders and vegetables), cereal-dairy breakfast-pattern (composed of milk, plain yogurt, unsweetened breakfast cereals, sorghum porridge and fruit juice, while being negatively correlated with maize meal porridge and saturated fats) and a processed food dietary pattern (composed of cheese, sweetened dairy products, candy/sugar, fast foods, alcoholic beverages, sugar-sweetened beverages, fruit spreads and crackers/potato crisps). While the traditionaland cereal-dairy breakfast dietary patterns were significantly inversely associated with breast cancer risk, no association was observed between a processed food dietary pattern and breast cancer risk (23) . However, this approach did not consider the degree of industrial food processing according to the NOVA system specifically.…”
mentioning
confidence: 79%
“…In this study, several patterns have been identified: a traditional pattern (composed of poultry, organ and offal meat, mono-and polyunsaturated fats, soup powders and vegetables), cereal-dairy breakfast-pattern (composed of milk, plain yogurt, unsweetened breakfast cereals, sorghum porridge and fruit juice, while being negatively correlated with maize meal porridge and saturated fats) and a processed food dietary pattern (composed of cheese, sweetened dairy products, candy/sugar, fast foods, alcoholic beverages, sugar-sweetened beverages, fruit spreads and crackers/potato crisps). While the traditionaland cereal-dairy breakfast dietary patterns were significantly inversely associated with breast cancer risk, no association was observed between a processed food dietary pattern and breast cancer risk (23) . However, this approach did not consider the degree of industrial food processing according to the NOVA system specifically.…”
mentioning
confidence: 79%
“…Among the main risk factors, dietary factors have garnered considerable attention ( 4 ). A substantial amount of epidemiological studies have been conducted to assess the impact of diet, a key modifiable risk factor on breast cancer risk ( 5 , 32 35 ). However, the majority of these studies have largely focused on the effect of the intakes of individual nutrients, foods or food groups ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple risk factors contribute to increased risk of breast cancer including alcohol intake, obesity, a sedentary lifestyle, family history, menstrual and reproductive history, exogenous hormone intake and never giving birth or breastfeeding have been well established ( 4 ). Along with these aforementioned risk factors, diet factors have been identified as important and modifiable risk factors in the development of breast cancer ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of metabolic acidosis was 62.4 % in advanced CKD and 46.6 % in early CKD; this prevalence is higher than the 33% - 40% among patients with CKD stage 3 – 4 from other continents (14, 40, 41). The possible explanation could be firstly, the more rapid CKD progression which has been shown to occur in black patients even early in their CKD stages (16, 28) and secondly, diet where replacement of traditional diets with contemporary/ western foods which contain mainly animal proteins, less vegetables and low intake of fruits might increase CKD patients’ dietary acid load (29, 42-45). Patients with low serum bicarbonate levels were 2-fold more likely to have advanced CKD, as reported also in other studies (14, 15).…”
Section: Discussionmentioning
confidence: 99%
“…The illiterate account for 7% of the population and 3.4% has only primary school education, and 29% of residents live in informal dwellings. Due to increased urbanization, there has been increased use of westernized dietary patterns often comprising of fast and deep-fried foods, processed meats, saturated fats, sugar sweetened beverages, alcoholic beverages plus other highly processed foods, unlike in rural areas where the traditional dietary patterns are predominant (29).…”
Section: Methodsmentioning
confidence: 99%